Avaliação do efeito do citral na dor neuropática e na inflamação - Nishijima, Catarine Massucato [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Injuries to the system peripheral nervous that result in neuropathic pain may evolve substantial functional loss and decreased quality of life of patients by permanent loss of sensory-motor functions. Surgeries such as breast, cardiac, thoracic, abdominal surgeries, caesarean and amputations culminate with the acute postoperative pain (APP) followed by persistent pain. Approximately 10% of patients develop chronic pain lasting between 3-6 months after surgery. The sensation of pain is exacerbated by simple activities such as walking, coughing and innocuous stimuli as touch and temperature. Another clinical condition investigated in this work is the chronic pain in Complex Regional Pain Syndrome type I (CRPS- I). CRPS- I is a multifactorial chronic neuropathy, resulting from deep tissue injury such as sprains, fractures, tourniquet, heart attack, stroke and vascular changes as Raynaud's phenomenon. The clinical management of neuropathic pain is complex, since it shows refractory to medications available, so this is the reason to evaluation of new agents with potential antinociceptive. Citral, a terpene widely found in essential oils of lemongrass, melissa, among other species, have been studied for its pharmacological properties, such as its agonist effect on channels TRP (transient receptor potential). In this work, we found that citral, at the doses of 100 mg/kg and 300 mg/kg (p.o), has antinociceptive and antiinflammatory in models of acute nociception and inflammation (formalin test, hot plate, acute postoperative pain and edema xylene -induced ear) without modifying the coordination and locomotor performance of the animals. Mice have exhibited a reduction of nociceptive threshold in chronic pain models after ischemia and reperfusion and partial sciatic nerve constriction with a maximal effect obtained at the dose of 100 mg/kg (p.o.) between 1 and 2 hours after administration. Citral (100 mg/kg, p.o.) was able to inhibit the licking ...

Lesões do sistema nervoso periférico que resultam em dor neuropática podem evoluir em substancial perda funcional e diminuição da qualidade de vida do paciente pelo permanente prejuízo das funções sensório-motoras. Cirurgias comuns tais como cirurgia da mama, cirurgias cardíacas, torácicas, abdominais, cesarianas e amputações culminam com o quadro de dor aguda pós-operatória (DPO) seguida de dor persistente. Aproximadamente 10 % dos pacientes evoluem para dor crônica com duração entre 3 a 6 meses após a cirurgia. A sensação dolorosa é exacerbada por atividades cotidianas como caminhar, tossir e por estímulos inócuos como toque e temperatura. Outra condição clínica investigada no presente trabalho é a dor crônica na Síndrome da Dor Complexa Regional do tipo I (SDCR-I). SDCR-I é uma neuropatia crônica de origem multifatorial, decorrente de injúria tecidual profunda tais como torções, fraturas, utilização de torniquete, infarto, acidente vascular encefálico e alterações vasculares como no fenômeno de Raynaud. A condução clínica da dor neuropática é complexa, uma vez que ela se mostra refratária a maioria dos medicamentos analgésicos disponíveis no mercado, razão pela qual existe um grande interesse na avaliação de novos agentes com potencial anti-nociceptivo. Citral, um terpeno amplamente encontrado em óleos essenciais de capim-cidreira, melissa, citronela, entre outras espécies vegetais, tem se destacado pelas suas propriedades farmacológicas, dentre elas seu efeito agonista em canais TRPs (receptor de potencial transitório). Neste trabalho constatamos que citral nas doses de 100 mg/kg e 300 mg/kg (p.o) apresenta atividade antinociceptiva e anti-inflamatória em modelos agudos de nocicepção e inflamação (teste da formalina, placa quente, dor aguda pós-operatória e edema de orelha induzido por xilol) sem alterar a coordenação e a performance locomotora dos animais. Animais ...
Keywords: Sistema nervoso - Ferimentos e lesões; Neuropatia; Dor pós-operatória; Terpenos; Postoperative pain